Pemanfaatan Set-Top Box Sebagai Remote Gateway Dengan VPN Tailscale Untuk Keamanan Jaringan - Jemy Arieswanto; Muhammad Rizki Nur Asyifa; Febry Lodwyk Rihe Riwoe (LPPM IBI Kesatuan, 2025)
The advancement of network technology has significantly increased the demand for secure remote access, especially among Small and Medium Enterprises (SMEs) with limited infrastructure and budgets. This research aims to design and implement a remote gateway system using a Set-Top Box (STB) running Linux Armbian OS, integrated with Tailscale VPN to offer a cost-effective and secure remote access solution. The research follows the Network Development Life Cycle (NDLC) method, which includes analysis, design, implementation, testing, monitoring, and system management. The STB is configured as a remote gateway enabling internal devices to be accessed externally via a Zero Trust-based VPN. During the implementation, IP forwarding and subnet routing are configured, and connectivity tests are carried out across Tailscale nodes. Test results show that the system delivers stable remote desktop access with an average bitrate of ≥2 Mbps and supports file and printer sharing with average transfer speeds between 6 to 8 Mbps. Security testing using Wireshark revealed no leaks of payload or metadata, confirming all traffic is encrypted by the WireGuard protocol. Additionally, monitoring showed the STB consumes minimal power, making it an ideal green computing solution for SMEs. The system proves to enhance operational efficiency with low energy and cost, while also providing a free alternative to previously used paid remote access tools.